Progress in the Chemistry of Organic Natural Products 106 - Kinghorn, A. Douglas; Falk, Heinz; Gibbons, Simon; Kobayashi, Jun'ichi (Progress in the Chemistry of Organic Natural Products,, 2017)
The first contribution presents coumarins, the largest group of 1-benzopyran derivatives found in plants. Coumarin chemistry remains one of the major interest areas of phytochemists, especially because of their structural diversity and medicinal properties, along with the wide-ranging bioactivities of these compounds, inclusive of analgesic, anticoagulant anti-HIV, anti-inflammatory, antimicrobial, antineoplastic, antioxidant, and immunomodulatory effects. The second contribution presents a comprehensive survey of the many aspects of PAD biochemistry and physiology. The third contribution gives a comprehensive overview of secondary metabolites from higher fungi, with more than 700 references highlighting the isolation, structure elucidation, biological activities, chemical synthesis, and biosynthesis of pigments, nitrogen-containing compounds, and terpenoids from mushrooms. .